Carotenoid-to-bacteriochlorophyll energy transfer through vibronic coupling in LH2 from Phaeosprillum molischianum - Thyrhaug, Erling; Lincoln, Craig N; Branchi, Federico; Cerullo, Giulio; Perlík, Václav; Šanda, František; Lokstein, Heiko; Hauer, Jürgen (Photosynthesis research, 2018)
The peripheral light-harvesting antenna complex (LH2) of purple photosynthetic bacteria is an ideal testing ground for models of structure-function relationships due to its well-determined molecular structure and ultrafast energy deactivation. It has been the target for numerous studies in both theory and ultrafast spectroscopy; nevertheless, certain aspects of the convoluted relaxation network of LH2 lack a satisfactory explanation by conventional theories. For example, the initial carotenoid-to-bacteriochlorophyll energy transfer step necessary on visible light excitation was long considered to follow the Förster mechanism, even though transfer times as short as 40 femtoseconds (fs) have been observed. Such transfer times are hard to accommodate by Förster theory, as the moderate coupling strengths found in LH2 suggest much slower transfer within this framework. In this study, we investigate LH2 from Phaeospirillum (Ph.) molischianum in two types of transient absorption experiments-with narrowband pump and white-light probe resulting in 100 fs time resolution, and with degenerate broadband 10 fs pump and probe pulses. With regard to the split Qx band in this system, we show that vibronically mediated transfer explains both the ultrafast carotenoid-to-B850 transfer, and the almost complete lack of transfer to B800. These results are beyond Förster theory, which predicts an almost equal partition between the two channels.
Keywords: Excitons; časové faktory; Ultrafast spectroscopy; světlosběrné proteinové komplexy; Time Factors; Fourierova analýza; přenos energie; LH2; Photosynthesis; Energy Transfer; Light-Harvesting Protein Complexes; Lasers; Spectrophotometry, Ultraviolet; Proteobacteria; Carotenoids; Bacteriochlorophylls; bakteriochlorofyly; lasery; karotenoidy; spektrofotometrie ultrafialová; Fourier Analysis; Excitation energy transfer